Gender, Religion and Educational Attainment: a Micro Level Analysis of Malda District, West Bengal. - Siddiqui, Farasat Ali and Hussain, Nazmul (2010)
The present paper is an attempt to analyse educational attainment by sex and religion. It is based on primary data generated through stratified random sampling with the selection of 80 villages at five per cent from rural areas and seven mohallas from the urban areas of Malda district during January to June 2009. A total of 10 per cent households (2,390 rural and 200 urban) were surveyed. The educational attainment in Malda district at the block level is analysed with special emphasis on females (literacy rate, educational attainment and enrolment). The study reveals that Hindu women have a better educational status compared to Muslim women at the household level while the situation is the reverse in gender gap. Inter-block disparity is rampant in the district. Blocks such as Bamongola and Gazol, in spite of having good educational facilities, have not been able to transform the development efforts to bridge the gender gap in education. Blocks with high literacy rates have a low male-female literacy gap in both religions. The higher the literacy, the higher is the female work participation rate. The female enrolment rate is below the male rate in spite of universalization of primary education and provision of mid-day meal schemes. The paper concludes that socio-religious norms and educational facilities hinder women’s education in particular and empowerment in general. Progress in women’s education has been achieved through government programmes and NGOs’ efforts.